Secrets according to Humphrey - Birney, Betty G. (Birney, Betty G. Humphrey adventures., 2014)
Humphrey, the pet hamster of Longfelow School's Room 26, learns that his classroom is full of secrets, the most important of which is that a student will be leaving soon.